2019
DOI: 10.1021/acsbiomaterials.9b01068
|View full text |Cite
|
Sign up to set email alerts
|

3D Tissue-Engineered Tumor Model for Ewing’s Sarcoma That Incorporates Bone-like ECM and Mineralization

Abstract: The tumor microenvironment harbors essential components required for cancer progression including biochemical signals and mechanical cues. To study the effects of microenvironmental elements on Ewing’s sarcoma (ES) pathogenesis, we tissue-engineered an acellular three-dimensional (3D) bone tumor niche from electrospun poly­(ε-caprolactone) (PCL) scaffolds that incorporate bone-like architecture, extracellular matrix (ECM), and mineralization. PCL-ECM constructs were generated by decellularizing PCL scaffolds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Similarly, Santoro et al emphasized the role of IGF1/IGF-1R pathway and biomechanical TME stimulation in drug resistance by using similar 3D models [113] . These data are in agreement with the recent study published by Molina et al [114] . Indeed, these authors demonstrated that 3D TME favoured the downregulation of IGF-1R via mTOR pathway, which was accompanied by a reduction of the clathrin-dependent nuclear localisation and transcription activity of IGF-1R [114] .…”
Section: D Culture Methods Of Primary Bone Tumourssupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, Santoro et al emphasized the role of IGF1/IGF-1R pathway and biomechanical TME stimulation in drug resistance by using similar 3D models [113] . These data are in agreement with the recent study published by Molina et al [114] . Indeed, these authors demonstrated that 3D TME favoured the downregulation of IGF-1R via mTOR pathway, which was accompanied by a reduction of the clathrin-dependent nuclear localisation and transcription activity of IGF-1R [114] .…”
Section: D Culture Methods Of Primary Bone Tumourssupporting
confidence: 94%
“…These data are in agreement with the recent study published by Molina et al [114] . Indeed, these authors demonstrated that 3D TME favoured the downregulation of IGF-1R via mTOR pathway, which was accompanied by a reduction of the clathrin-dependent nuclear localisation and transcription activity of IGF-1R [114] . TC-71 3D culture was exposed to different shear stresses close to those observed in bone microenvironment in a flow perfusion bioreactor.…”
Section: D Culture Methods Of Primary Bone Tumourssupporting
confidence: 94%
“…Thus, in vitro 3D environments enhance the canonical IGF-IR signal cascade's attenuation through mechanistic target of rapamycin (mTOR). Notably, 3D environments facilitated a decrease in the clathrin-dependent nuclear localization and transcriptional activity of IGF-IR [159]. Therefore, modulating the matrix network could contribute to cancer therapies directed at the IGF-signaling pathway.…”
Section: Matrix Effectors Modulate Igf/igf-ir Pathway Restricted Signalingmentioning
confidence: 99%
“…While biomaterials can be natural or artificially made [ 89 ], most 3D tumor models use natural biomaterials purified from animals or plants that can be enzymatically digested by tumor and/or stromal cells. The selection of the biomaterial to be used as a scaffold for 3D tumor modeling is far from trivial as some are biologically active (e.g., ECM components driving cancer growth [ 89 ]) and can offer specific advantages, such as sustaining drug release or generating bone-like structures [ 90 , 91 ]. Commonly used natural biomaterials in 3D tumor models include collagen, gelatin, Matrigel, hydrogel, chitosan, alginate, silk, poly-ε-caprolactone (PCL), and hyaluronic acid [ 89 , 92 , 93 ].…”
Section: Modeling the Tumor Microenvironmentmentioning
confidence: 99%
“…Beyond that, some studies have also reported engineering biomaterials to have specific functions. For example, gelatin hydrogel microspheres (GM) have been used as a source to continually release drugs [ 90 , 94 ]; PCL scaffolds have been engineered to have bone-like architecture and mineralization [ 91 , 95 ].…”
Section: Modeling the Tumor Microenvironmentmentioning
confidence: 99%